Environmental behaviors of microplastics in aquatic systems: A systematic review on degradation, adsorption, toxicity and biofilm under aging conditions - Luo, Hongwei; Liu, Chenyang; He, Dongqin; Xu, Juan; Sun, Jianqiang; Li, Jun; Pan, Xiangliang (Journal of hazardous materials, 2022)
Microplastics (MPs, < 5 mm) in the environment have attracted worldwide attention due to their wide distribution and difficulty in handling. Aging processes such as UV irradiation, biodegradation, physical abrasion and chemical oxidation can affect the environmental behavior of MPs. This review article summarizes different aging processes of MPs and subsequent effects on the adsorption of pollutants, the leaching of additives, and the toxicity of MPs. In addition, the formation process of biofilm on the surface of MPs and the interactions between biofilm and aged MPs are revealed. MPs can accumulate different environmental pollutants (organic pollutants, heavy metals, microorganisms, etc.) through surface adsorption, pore filling and distribution. Moreover, the aging of MPs affects their adsorption performance toward these pollutants due to a series of changes in their specific surface area and oxygen-containing functional groups. The release of some toxic additives such as phthalates after aging can enhance the toxic effects of MPs. Aging also changes the shape and size of MPs, which can affect the eating habits of the organisms and further increase the potential toxicity of MPs. This article conducts a systematical analysis and summary of the environmental behavior and physicochemical properties of MPs as well as the changes due to MPs aging, which helps to better understand the impact of aging on MPs in the environment. Future research on MPs aging should reduce the knowledge gap between laboratory simulation and actual conditions and increase the environmental relevance. [Display omitted] •Aging of MPs causes their surface polarity, hydrophilicity and charge to change.•Aging of MPs affects their adsorption performance toward environmental pollutants.•Aging accelerates the release of additives and enhances the toxic effects of MPs.•Biofilm formation on MPs and biofilm interactions with aged MPs are elucidated.